Elder abuse in culturally and linguistically diverse communities: Developing best practice - Blundell, Barbara; Clare, M. (Centre for Vulnerable Children and Families, The University of Western Australa, 2012)
This study explores and identifies ‘best practice’ in service delivery with older Australians at risk of elder abuse, whose first language is not English. This report includes a review of State, national and international research literature and government reports addressing this complex personal, family, community and political problem. One hundred and fifty-two older people from culturally and linguistically diverse communities (CALD) took part in one of eight language group community forums which included speakers of Polish, Italian, Cantonese, Mandarin, Iranian, Vietnamese, a group of people of Sikh culture, and a mixed group of Indian, Pakistani, Burmese and Sri Lankans. Participants in the last groups spoke good English, and an interpreter was present at all other forums. Fifteen professionals also participated in a series of three focus groups exploring the topic. The study concluded that the current Western Australian policy and practice context was limited by over-emphasising reactive rather than proactive measures towards addressing elder abuse. It also proposed that services for vulnerable people who cannot speak and/or read English are inadequate for the current level of service demand and the predicted increases in demand from older CALD Australians.